How dry can it get? the use of anterior segment optical coherence tomography in the research and management of dry eye. - Lee, Man Xin. (2011)
Dry eye is a condition that has significant morbidity. While there exists a myriad of diagnostic tests to monitor dry eye, most of them do not correlate with each other or have poor repeatability. Anterior Segment Optical Coherence Tomography (AS-OCT), an instrument that can measure tear meniscus height (TMH) and area (TMA), had been shown to be repeatable, sensitive, specific and non-invasive in the diagnosis of dry eye. Here we evaluate AS-OCT applicability in dry eye drug trials. AS-OCT tear meniscus measurements were correlated with other diagnostic test at baseline. While TMH and TMA correlated with each other, only Schirmer I test, among other tests, was found to correlate with TMH and TMA except inferior TMA. Intra-observer repeatability for measuring each scan was found to be consistent for both TMH and TMA measurements. No statistically significant differences were found in the TMH and TMA pre- and post-treatment or between treatment groups (p>0.05). Altogether, the results suggest that AS-OCT can be included in longitudinal dry eye studies to validate Schirmer I test. We also compared the repeatability between scans of the newer Cirrus AS-OCT with the older Visante AS-OCT and preliminary results suggest Cirrus has better repeatability.